Решите уравнения: 2x^2 − 4√2x + 3 = 0 x^2 − x(√7−2) − 2√7 = 0 2x^2 − 4x − 17 = 0

0 голосов
37 просмотров

Решите уравнения:

2x^2 − 4√2x + 3 = 0
x^2 − x(√7−2) − 2√7 = 0
2x^2 − 4x − 17 = 0


Алгебра (448 баллов) | 37 просмотров
Дан 1 ответ
0 голосов

2х²-4√2х+3=0
 х=(2√2+-√(8-6))\2=(2√2+-√2)\2   х=0,5√2   х=1,5√2

х²-(√7-2)х-2√7=0
х=(2-√7+-√(4-4√7+7+2√7))\2=(2-√7+-√(11-2√7))\2  х=(2-√7-√(11-2√7))\2                                                                                          х=(2-√7+√(11-2√7))\2

2х²-4х--17=0
х=(2+-√(4+34))\2=(2+-6)\2    х=-2  х=4

(7.7k баллов)